Production of Crispy Pupae Silkworm Using Drying of Microwave Combined with Hot Air - Paengkanya, Suwit; Nathakaranakule, Adisak; Soponronnarit, Somchart (Burapha Science Journal, 2026)
Crispy insect and worm are popular foods, but contain a lot of oil which is not good for health. Therefore, the objective of this research was to produce crispy pupae silkworm using microwave combined with hot air (MWHA) and hot air (HA) drying method. The drying kinetics, specific energy consumption (SEC) of the drying processes and the qualities of the dried product in terms of color, texture, water activity, and microstructure were evaluated. The pupae silkworm was dried using MWHA drying method at 150, 200, 250 and 300 W combined with HA at 65 oC, air velocity of 0.3 m/s and circulating air of 80%. The sample was dried until the moisture content was approximately 4% (d.b.) and compared with those dried by the HA drying at 65 oC. The results showed that all cases of pupae silkworm dried by MWHA had higher drying rates than those under the HA, resulting in shorter drying time and lower SEC of drying process. Increasing the microwave power level increased the drying rate and reduced the SEC of the drying process. The dried pupae silkworm from MWHA had more lightness and larger pore size but had lower in redness (+a*), yellowness (+b*) and hardness than dried pupae from HA. The increase of the microwave power causes the dried pupae to have low hardness, more crispiness, but not effect on the color values. The dried pupae silkworm from all experimental cases had lower water activity than 0.6, conforming to standards and safe for storage. The recommended condition for drying pupae silkworms using MWHA is a microwave power of 300 W combined with HA at 65 oC.